Comparison of Air Abrasion and Mechanical Decontamination for Managing Inflammatory Reactions around Dental Implants: A Systematic Review and Meta-Analysis - Ki-Jung Jang; Ahrim Lyu; Sung-Hoon Han; Na Jin Kim; Saet-Byeol Han; Hye-Jung Song; Won-Jong Park; Jun-Beom Park (Applied Sciences, 2024)
Background: A number of mechanical decontamination methods have been proposed, however, there is no agreed-upon gold standard among them. This study aims to conduct a meta-analysis to assess the differences in the management of an inflammatory reaction around dental implants between air abrasion and mechanical decontamination. Methods: A comprehensive search strategy was employed, incorporating controlled vocabulary (MeSH) and free-text terms. This search was conducted by two reviewers to identify published systematic reviews. Three major electronic databases, namely, Medline via PubMed, the Cochrane database, and Embase, were searched up to May 2024. Results: Initially, 300 articles were identified. After conducting a comprehensive search and applying strict inclusion criteria, a total of 13 studies were deemed eligible for inclusion in the meta-analysis. The results showed that the mean difference in probing depth between air abrasion and other mechanical decontamination was 0.28 (95% confidence interval, −0.20 to 0.76). The mean difference in probing depth of air abrasion compared with other mechanical decontamination in maintenance purposes was 1.05 (95% confidence interval, 0.18 to 1.91). The mean difference in bleeding on probing between air abrasion and other mechanical decontamination was 0.51 (95% confidence interval, 0.07 to 0.95). The mean difference in alveolar bone loss between air abrasion and other mechanical decontamination was −0.14 (95% confidence interval, −0.77 to 0.48). The mean difference in alveolar bone loss for surgical approaches of air abrasion compared with other mechanical decontamination was 0.32 (95% confidence interval, 0.03 to 0.61). Conclusions: The findings of the study indicate that the use of air abrasion was just as effective as other mechanical decontamination methods in reducing probing depth and alveolar bone loss. The subgroup analysis showed that air abrasion was less effective in reducing probing depth in maintenance purposes. Additionally, air abrasion was less effective in reducing alveolar bone loss in surgical approaches.